Profitability of Islamic Commercial Banks in Indonesia: Third-Party Funds Analysis and Financing - Rahmat, Rahmat Kurnia; Yoshanti, Ghita; Maminirina Fenitra, Rakotoarisoa (LPPM Universitas Terbuka, 2023)
This research aims to examine the correlation of Third Party Funds and Financing on the Profitability of Islamic Commercial Banks in Indonesia. The gap of this research is the different findings of the financial reports of Islamic Commercial Banks in Indonesia data for the 2018-2022 period, where the growth of Return On Assets (ROA) in third-party funds and financing is not always ideally balanced. This research elaborates on the profitability of Islamic Commercial Banks through Return On Assets (ROA). The data collection for this research is utilizing Secondary Research from the Islamic Commercial Bank financial report 2018-2022 period combined with a descriptive quantitative method with the help of Eviews 12 software. The result shows that third-party funds and financing have no significant effect on the profitability of Islamic Commercial Banks per se. Meanwhile, surprisingly third-party funds and financing altogether, simultaneously have a significant effect on profitability in Islamic Commercial Banks.